A Beginner’s Guide to Begonias: Vegetative Propagation - Julian Ginori; Heqiang Huo; Zhanao Deng; Sandra Wilson (EDIS)
This new 4-page publication of the UF/IFAS Environmental Horticulture Department is written for Florida nursery operators, landscape professionals, and individuals interested in propagating their own begonias. It goes into detail on how to multiply begonias via vegetative propagation. Written by Julian Ginori, Heqiang Huo, Zhanao Deng, and Sandra Wilson. https://edis.ifas.ufl.edu/ep621